Association between high-risk fertility behaviour and anaemia among urban Indian women (15-49 years) - Sanjay Kumar Pal; Chander Shekhar (BMC, 2024)
Abstract Background Women in their reproductive age have tremendous health implications that affect their health and well-being. Anaemia is an indicator of inadequate dietary intake and poor health. Maternal malnutrition significantly impacts maternal and child health outcomes, increasing the mother's risk of dying during delivery. High-risk fertility behaviour is a barrier to reducing mother and child mortality. This study aims to examine the level of high-risk fertility behaviour and anaemia among ever-married urban Indian women and also examine the linkages between the both. Methods Based on the National Family Health Survey's fifth round of data, the study analyzed 44,225 samples of ever-married urban women. Univariate and bivariate analysis and binary logistic regression have been used for the analysis. Results Findings suggested that more than half (55%) of the urban women were anaemic, and about one-fourth (24%) of women had any high-risk fertility behaviour. Furthermore, the results suggest that 20% of women were more vulnerable to anaemia due to high-risk fertility behaviour. For the specific category, 19% and 28% of women were more likely to be anaemic due to single and multiple high-risk fertility. However, after controlling for sociodemographic factors, the findings showed a statistically significant link between high-risk fertility behaviour and anaemia. As a result, 16% of the women were more likely to be anaemic due to high-risk fertility behaviour, and 16% and 24% were more likely to be anaemic due to single and multiple high-risk fertility behaviour, respectively. Conclusions The findings exposed that maternal high-risk fertility behaviour is a significant factor in raising the chance of anaemia in ever-married urban women of reproductive age in forms of the short birth interval, advanced maternal age, and advanced maternal age & higher order. Policy and choice-based family planning techniques should be employed to minimize the high-risk fertility behaviour among Indian urban women. This might aid in the reduction of the malnutrition status of their children.